High throughput screening system for engineered cardiac tissues - Ma, Marshall S.; Sundaram, Subramanian; Lou, Lihua; Agarwal, Arvind; Chen, Christopher S.; Bifano, Thomas G. (Frontiers in Bioengineering and Biotechnology, 2023)
Three dimensional engineered cardiac tissues (3D ECTs) have become indispensable as in vitro models to assess drug cardiotoxicity, a leading cause of failure in pharmaceutical development. A current bottleneck is the relatively low throughput of assays that measure spontaneous contractile forces exerted by millimeter-scale ECTs typically recorded through precise optical measurement of deflection of the polymer scaffolds that support them. The required resolution and speed limit the field of view to at most a few ECTs at a time using conventional imaging. To balance the inherent tradeoff among imaging resolution, field of view and speed, an innovative mosaic imaging system was designed, built, and validated to sense contractile force of 3D ECTs seeded on a 96-well plate. Results have shown real-time, parallel contractile force monitoring for up to 3 weeks. Pilot drug testing was conducted using isoproterenol. The described tool increases contractile force sensing throughput to 96 samples per measurement; significantly reduces cost, time and labor needed for preclinical cardiotoxicity assay using 3D ECT. More broadly, our mosaicking approach is a general way to scale up image-based screening in multi-well formats.